The Derivation of the Interrogative ה in hebrew - Davis, Ryan Conrad (Hebrew studies, 2018)
This article offers a new proposalfor the derivation of the interrogative ה. There have been numerous proposals for the derivation of the interrogative ה, but none have gained wide acceptance. Through internal reconstruction, I will demonstrate that the interrogative ה in Hebrew can be traced back to two forms, *ha- and *haC-. I propose *ha- is a common Central Semitic form that was inherited by Arabic, Hebrew, and Aramaic, but that *haC- is derivedfrom the particle *han-. *Han- is connected to a set of presentative particles (*hā, *han, *hal) that each independently developed into interrogatives in other Central Semitic languages.